Pengaruh Adopsi IFRS, Pemberian Informasi Nilai Wajar, dan Pengungkapan Jasa Penilai Terhadap Asimetri Informasi Pada Emiten di Indonesia [Impact of IFRS Adoption, Fair Value Information, and Disclosure of Appraiser Services on the Information Asymmetry of Firms in Indonesia] - Felisia Novita Sari; Dedhy Sulistiawan; Aurelia Carina Sutanto (Universitas Pelita Harapan, 2015)
This study evaluates the impact of IFRS adoption, fair value information of property, plant, and equipment (PPE), and disclosure of appraiser services into a firm's information asymmetry. Information asymmetry is the primary reason for the existence of accounting. Accounting could be a mechanism to enable communication of useful information from insiders to outsiders. IFRS adoption and better disclosure are important factors that avoid exploitation by informed bodies, and protect uninformed investors. Using Indonesian data, this study analyzes two year before and after 2011, an implementation year. This research gives evidence that IFRS adoption is able to decrease information asymmetry. Disclosure of appraiser services is also able to decrease information asymmetry, however, fair value information of PPE is not an important determinant of information asymmetry. Other results present that share prices, share turnover, and firm size can affect information asymmetry. By knowing the factors affecting information asymmetry, information asymmetry problem could be minimized. This study concludes that IFRS implementation and disclosure of appraiser services affect information asymmetry.